Confirmatory Factor Analysis of the DASS-18 Scale for Assessment of Depression, Anxiety, and Stress Symptoms - Syahputra, Yuda; Hafni, Merri; Solihatun, Solihatun; Istiana, Istiana; Rahmat, Candra Prasiska; Karisma, Sally Putri; Erwinda, Lira (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
Mental health is a crucial aspect of individual well-being, and accurate assessment of psycholocccgical distress is important for effective prevention and intervention efforts. This study aims to test the validity and reliability of the Depression, Anxiety and Stress Scale-18 (DASS-18) in the context of the Indonesian population. DASS-18 was tested on 170 students aged 13-14 years spread throughout Indonesia. Confirmatory factor analysis (CFA) was used to validate the DASS-18 factors, using a number of indices to measure model fit. The results of the analysis show that the DASS-18 is a valid and reliable tool for measuring psychological distress, with each factor showing excellent reliability. In addition, the significant positive relationships between DASS-18 factors, such as stress-anxiety, stress-depression, and anxiety-depression, underscore the close interconnection between these constructs